Performance Evaluation of MRMED Algorithm by Monitoring BER - SYED RIZWAN-UL-HASAN; Muhammad Tahir (Sir Syed University Research Journal of Engineering and Technology)
In this research work, we have developed a communication system (transmitter / receiver) to control peak to average power (PAPR) with  small bit error rate (BER) for a 4G system called multicode code division multiple access (MCCDMA). Proposed communication system works on modified Reed Muller encoded data (MRMED) string. In MRMED data is first encoded with Reed Muller (RM) code. Thereafter, encoded RM message is XORed with optimal binary string, which results lower Peak to Average Power ratio (PAPR).  A well-known fact is that, bit error rate (BER) is the best performance measurement tool for a communication system. To check the integrity of our communication system, we have run the simulation for monitoring BER using MRMED sequence. Simulation work conducted, with multipath Rayleigh fading, Minimum Shift Keying (MSK) modulation and several orders of RM codes. Our results show that implementing MRMED sequences of the suggested MCCDMA communication structure, returns noticeable lower BER. For instance, in case of RM(1,4), that has error improvement proficiency of 3 (three) errors , returns BER = 8.2x10−5 adopting MSK, at SNR = 12dB. Similarly, for RM(2,3), which has error improvement efficiency of 0  error and shows distinct BER of 4.9x10−4 at  12dB (SNR).In addition to using simulation for checking BER performance of our communication system, we have also shown in our results that, as the error improvement capability of different RM codes surges, correspondingly we get a lower BER.